2022
DOI: 10.1038/s41419-022-04924-4
|View full text |Cite|
|
Sign up to set email alerts
|

Involvement of FSP1-CoQ10-NADH and GSH-GPx-4 pathways in retinal pigment epithelium ferroptosis

Abstract: Retinal pigment epithelium (RPE) degeneration plays an important role in a group of retinal disorders such as retinal degeneration (RD) and age-related macular degeneration (AMD). The mechanism of RPE cell death is not yet fully elucidated. Ferroptosis, a novel regulated cell death pathway, participates in cancer and several neurodegenerative diseases. Glutathione peroxidase 4 (GPx-4) and ferroptosis suppressor protein 1 (FSP1) have been proposed to be two main regulators of ferroptosis in these diseases; yet,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Ferroptosis is regulated by numerous pathways and implicated in many diseases. In addition to the mechanisms mentioned above, there are other possible mechanisms which have been proposed, such as the antioxidant mechanisms which include GPX4 pathway [36], FSP1 pathway [37], and other pathways. FSP1-NADPH-CoQ pathway [38] and nuclear factor erythroid 2-related factor 2 (Nrf2) pathway are potential regulatory pathways of ferroptosis [39].…”
Section: Other Mechanismsmentioning
confidence: 99%
“…Ferroptosis is regulated by numerous pathways and implicated in many diseases. In addition to the mechanisms mentioned above, there are other possible mechanisms which have been proposed, such as the antioxidant mechanisms which include GPX4 pathway [36], FSP1 pathway [37], and other pathways. FSP1-NADPH-CoQ pathway [38] and nuclear factor erythroid 2-related factor 2 (Nrf2) pathway are potential regulatory pathways of ferroptosis [39].…”
Section: Other Mechanismsmentioning
confidence: 99%
“…It has been proven that TBI-induced neuronal necrosis and parenchymal hemorrhage release a large amount of free iron into the peripheral space, which further leads to ferroptosis due to excessive oxidative damage to neurons and glial cells [ 7 , 8 ]. Increased levels of antioxidant factors exert protective roles against ferroptosis [ 9 , 10 ], further indicating that ferroptosis is closely related to the disturbance of cellular redox homeostasis. Recent studies, including our own, have indicated that ferroptosis plays an important role in neuronal death and neural dysfunction after TBI [ 11 , 12 , 13 ], intracerebral hemorrhage [ 14 ], and spinal cord injury [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Zhang et al (2022b) reported that CoQ10 could improve oxidative stress, as indicated by the increased MDA concentration. Another report by Yang et al supported the functional regulatory effects of CoQ10 in ferroptosis, controlling sodium iodate-induced pathologies in vitro and in vivo (Yang et al, 2022b). However, the efficacy of CoQ10 as a ferroptosis-modulating agent against musculoskeletal disorders is not yet fully elucidated.…”
Section: Discussion and Future Remarksmentioning
confidence: 99%